Assessment of the structural properties of timber members in situ : a probabilistic approach - Machado, J. S. (2012)
The assessment of the structural performance of existing timber structures is dependent, among other factors, on the capacity to evaluate the physical and mechanical properties of structural timber elements in situ. This paper discusses the possibilities/advantages of using a probabilistic approach to obtain a more reliable prediction of the reference properties of these timber members in situ. The presented approach combines information from common non-destructive techniques (NDT), such as visual assessment and ultrasounds, and those from semi-destructive tests (SDT), as meso tension specimens and wood cores. An application of this approach to maritime pine (Pinus pinaster Ait.) and chestnut (Castanea sativa Mill.) timber pieces of structural dimension is presented.